The Rise of China: Navigating the New Era with Distinctive Strategies - Mubeen, Muhammad (Mandarinable: Journal of Chinese Studies, 2025)
The This study reviews China's approach to the new era and its implications for the global landscape. It explores the key aspects of China's approach, including its steadfast commitment to economic development, technological innovation, reshaping of global governance structures, and the challenges it faces. The analysis highlights China's remarkable economic transformation and integration with the global economy, driven by market-oriented reforms and initiatives such as the Belt and Road Initiative. It also underscores the importance of technological innovation as a priority, showcasing China's advancements in areas such as artificial intelligence, 5G technology, and quantum computing. Furthermore, the study delves into China's engagement with international organizations and the establishment of new multilateral institutions to reshape global governance. The implications of China's rise as a global power and its impact on existing power dynamics are discussed, along with the challenges it faces in navigating the new era, both domestically and externally. Overall, this examination provides insights into China's trajectory and its significance in shaping the future global landscape.